Association of kidney function with NMR-quantified lipids, lipoproteins, and metabolic measures in Mexican adults - Aguilar-Ramirez, D; Alegre-Díaz, J; Herrington, WG; Staplin, N; Ramirez-Reyes, R; Gnatiuc, L; Hill, M; Romer, F; Torres, J; Trichia, E; Wade, R; Collins, R; et al. (Oxford University Press, 2021)
Context Chronic kidney disease (CKD) and diabetes are associated with dyslipidaemia, metabolic abnormalities, and atherosclerotic risk. Nuclear magnetic resonance (NMR) spectroscopy provides much more detail on lipoproteins than traditional assays.